Uterine Transplantation: Review of Livebirths and Reproductive Implications. Issue 8 (August 2021) - Jones, Benjamin P.; Kasaven, Lorraine; Vali, Saaliha; Saso, Srdjan; Jalmbrant, Maria; Bracewell-Milnes, Timothy; Thum, Meen-Yau; Quiroga, Isabel; Friend, Peter; Diaz-Garcia, Cesar; Ghaem-Maghami, Sadaf; Yazbek, Joseph; et al.
Abstract : Uterine transplantation (UTx) is a fertility restoring treatment for women with absolute uterine factor infertility. At a time when there is no question of the procedure's feasibility, and as the number of livebirths begins to increase exponentially, various important reproductive, fetal, and maternal medicine implications have emerged. Detailed outcomes from 17 livebirths following UTx are now available, which are reviewed herein, along with contextualized extrapolation from pregnancy outcomes in other solid organ transplants. Differences in recipient demographics and reproductive aspirations between UTx and other transplant recipients make extrapolating management strategies and outcomes in other solid organ transplants inappropriate. Whereas preterm delivery remains prominent, small for gestational age or hypertensive disorders do not appear to be as prevalent following UTx when compared to other solid organ transplants. Given the primary objective of undertaking UTx is to achieve a livebirth, publication of reproductive outcomes is essential at this early stage, to reflect on and optimize the management of future cases.